2018
DOI: 10.3892/ol.2018.9344
|View full text |Cite
|
Sign up to set email alerts
|

Isoliquiritigenin inhibits cell proliferation and migration through the PI3K/AKT signaling pathway in A549 lung cancer cells

Abstract: The present study aimed to investigate the molecular mechanisms of inhibition of Isoliquiritigenin (ISL) on the proliferation and migration of A549 cells. A549 cells were cultured in vitro, and the effects of ISL inhibition were examined using cell counting kit-8, Transwell invasion and flow cytometric assays. Western blot analysis was also performed to detect cell apoptosis and the expression of phosphatidylinositol 3-kinase (PI3K)/AKT serine/threonine kinase (AKT) signaling pathway-associated proteins. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…In agreement with our findings, Peng et al reported that treatment of MDA-MB-231 cells with ISL induced cell apoptosis, and they observed an enhancement of the ratio of Bax to Bcl-2 by ISL treatment [37]. Moreover, ISL treatment was also observed to induce cancer cell apoptosis in lung cancer [38], uterine leiomyoma [39], and endometrial cancer [40].…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with our findings, Peng et al reported that treatment of MDA-MB-231 cells with ISL induced cell apoptosis, and they observed an enhancement of the ratio of Bax to Bcl-2 by ISL treatment [37]. Moreover, ISL treatment was also observed to induce cancer cell apoptosis in lung cancer [38], uterine leiomyoma [39], and endometrial cancer [40].…”
Section: Discussionsupporting
confidence: 92%
“…There is mounting evidence suggesting that the PI3K/ AKT signaling pathway plays an indispensable role in the regulation of cellular features such as survival, proliferation, and apoptosis. 37 The research of Tian et al 38 shows the PI3K/AKT pathway is involved in lung cancer cell proliferation and apoptosis. Fang et al 37 reveal that PI3K/ AKT signaling pathway plays an important role in kidney cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, this signaling network could be a major target in cancer inhibition. An imbalance in the PI3K/AKT pathway make an important contribution in the arrangement and growth of lung cancer, and the activation of the PI3K/AKT pathway can stimulate the transduction of many downstream signals and assist the growth of NSCLC [ 10 , 11 , 12 ]. Targeting such intracellular pathways that modulate proliferation, apoptosis, metastasis and resistance to chemotherapy shows a significant therapeutic approach for lung cancer.…”
Section: Introductionmentioning
confidence: 99%